Strengthening Public Legal Critical Awareness Through The Book Launch of "Mengapa Hukum Dipermainkan?" Why Is The Law Manipulated? - Zetria Erma; Ramadhany Nasution; Jenda Ingan Mahuli; Syawal Amry Siregar; Oktavianto Setyo Nugroho; Saimah Rambe (International Journal Of Community Service, 2026)
The low level of legal understanding among the public is one of the main reasons why law can easily be manipulated by those in power. Communities that are unaware of their rights tend to accept injustice without resistance. Arising from this condition, this community service activity was carried out through the launch and book discussion of "Mengapa Hukum Dipermainkan?" [Why Is the Law Manipulated?] by Eka Putra Zakran, SH., MH., as a means of education and strengthening the public’s critical attitude toward the existing legal system. The event was attended by participants from various backgrounds, ranging from students, community leaders, and members of advocate organizations to local government representatives. The implementation methods included an open book launch, a book discussion session, interactive discussions, and a direct question-and-answer session with the author and resource persons. The results showed a significant increase in participants’ understanding of their legal rights, as well as the growth of a critical attitude in evaluating law enforcement processes in their surroundings. This program is expected to serve as a starting point for the formation of a legally literate society that is willing to question injustice.